DNA repair genes play a variety of roles in the development of fish embryos - Dey, Abhipsha; Flajšhans, Martin; Pšenička, Martin; Gazo, Ievgeniia (Frontiers in Cell and Developmental Biology, 2023)
Embryogenesis is one of the most important life stages because it determines an organism’s healthy growth. However, embryos of externally fertilizing species, such as most fish, are directly exposed to the environment during development and may be threatened by DNA damaging factors (pollutants, UV, reactive oxygen species). To counteract the negative effects of DNA fragmentation, fish embryos evolved complex damage response pathways. DNA repair pathways have been extensively studied in some fish species, such as zebrafish (Danio rerio). Our literature review, on the other hand, revealed a paucity of knowledge about DNA damage response and repair in non-model aquaculture fish species. Further, several pieces of evidence underlie the additional role of DNA repair genes and proteins in organogenesis, spatiotemporal localization in different tissue, and its indispensability for normal embryo development. In this review, we will summarize features of different DNA repair pathways in course of fish embryo development. We describe how the expression of DNA repair genes and proteins is regulated during development, their organogenetic roles, and how the expression of DNA repair genes changes in response to genotoxic stress. This will aid in addressing the link between genotoxic stress and embryo phenotype. Furthermore, available data indicate that embryos can repair damaged DNA, but the effects of early-life stress may manifest later in life as behavioral changes, neoplasia, or neurodegeneration. Overall, we conclude that more research on DNA repair in fish embryos is needed.